Desempenho e características de carcaça de cordeiros Laucane alimentados com níveis de gordura protegida de óleo de palma - Cesco, Gabriela de Oliveira (2015)
The objective of this experiment was to evaluate performance, characteristics of carcasses and morphometry and loin tissue composition of Lacaune lambs fed with protected fat from palm oil at feedlot. Twenty eight males lambs were used, belonging to the genetic group Lacaune, after weaning and initial 21 kg weight, distributed in 4 treatments based on the inclusion of 0.0%, 2.0%, 4.0% and 6.0% of protected fat from palm oil supplied in the concentrate given to the animals. The diets were formulated to estimate gain of 250 g/day, isocaloric and isoproteic in proportion of 80% concentrate and 20% hay. When the animals reached 37 kg weight, were weighed and subjected to a water diet 18 hours after this period was performed to evaluate body condition and weight to obtain the live weight at slaughter. The lambs were slaughtered following the stunning method for electro and bleeding by sectioning the carotid arteries and jugular veins. After slaughter, complete carcass were stored in cold chamber at 2°C during 24 hours and then cut in half. The left side was divided in order to obtain commercial cuts: leg, loin, chuck, ribs, undercover ribs, breast and neck. Then, was measurements maximum muscle depth, maximum muscle width, minimum thickness of fat and maximum thickness of fat in the Longissimus lumborum. The loins was identified and frozen for later dissection. After the thawing in the refrigerator, there was the weighing of same and dissection, the tissue to determine the composition through the separation of muscle tissue, bone tissue and adipose tissue. There were no differences observed (P> 0.05) between feedlot periods (48 days), daily weight gains (330 g/day), body condition score (3.55), carcass weights hot (17.08 kg), weight of cold carcass (16.58 kg), yield commercial carcass (46.33%), losses in the cooling (2.93%), compactness index of the carcass (0.22 kg/cm²) and compactness index of the leg (0.51). The inclusion of different percents of protected fat from palm oil provided effect (P<0.05) cubic difference to yield of leg. There were no differences observed (P> 0.05) between weight of ½ carcass (8.29 kg), yield of chuck (18.20%), loin (10.86%), ribs (10.79%), undercover ribs (6.49%), breast (11.54%) and neck (9.06%). The variables of loin weight (745 g), loin eye area (12.19 cm²) and lower fat fat thickness (1.40 mm) were not modified (P>0.05) by levels of protected fat. The diet offered containing levels of protected fat altered (P<0.05) percentage of muscle tissue, fat, and skeletal, muscle tissue/bone, proportion of edible portion/bone and greater thickness greater fat. The inclusion of different percents of protected fat from palm oil no promote differences in performance and characteristics of carcasses of Lacaune lambs. Therefore not recommended the use of this product in the finishing feedlot lambs.